2011
DOI: 10.1371/journal.pone.0022878
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Winter and Summer Abundance of Cetaceans in the Pelagos Sanctuary (Northwestern Mediterranean Sea) Through Aerial Surveys

Abstract: Systematic long-term monitoring of abundance is essential to inform conservation measures and evaluate their effectiveness. To instigate such work in the Pelagos Sanctuary in the Mediterranean, two aerial surveys were conducted in winter and summer 2009. A total of 467 (131 in winter, 336 in summer) sightings of 7 species was made. Sample sizes were sufficient to estimate abundance of fin whales in summer (148; 95% CI = 87–254) and striped dolphins in winter (19,462; 95% CI = 12 939–29 273) and in summer (38 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 41 publications
(34 reference statements)
10
80
0
Order By: Relevance
“…Traditional line-transect surveys estimating abundance would search across depths (Buckland et al, 2001;Mellinger and Barlow, 2003;Barlow and Taylor, 2005; Panigada et al, 2011;Pirotta et al, 2011). However, because the principal goal of the RV Odyssey work was to get biopsy samples, the RV Odyssey surveyed specifically along the −2000 to −3000 m isobaths.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional line-transect surveys estimating abundance would search across depths (Buckland et al, 2001;Mellinger and Barlow, 2003;Barlow and Taylor, 2005; Panigada et al, 2011;Pirotta et al, 2011). However, because the principal goal of the RV Odyssey work was to get biopsy samples, the RV Odyssey surveyed specifically along the −2000 to −3000 m isobaths.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mobile animals may not use the entire suitable habitat at any one time (Boyce et al 2002); thus, it may be difficult to demonstrate non-use, especially in the case of small populations (ca. 3500 individuals in the western Mediterranean Sea; Forcada et al 1996, Panigada et al 2011. Lastly, in addition to the ecological knowledge taken into account, the spatial dimension of the model for optimizing the parameterization (distance to potential habitat as enhanced by Valavanis et al 2008) on a daily time scale and the ability to select optimal habitat size are key predictive elements which are not present in most regression models.…”
Section: Selection Of Methods and Predictorsmentioning
confidence: 99%
“…1a) was estimated at 715 individuals (CV ¼ 31.2%) (Gannier, 2006). Surveys carried out in summer 2009 in the Pelagos Sanctuary estimated abundance of fin whales at 148 (95% CI ¼ 87e254), pointing towards an appreciable decrease in summer abundance and density since the early 1990s (Panigada et al, 2011). Studies on Mediterranean fin whales feeding habits inferred from surface feeding visual observations from stomach content and faeces analyses suggested that the euphausiid Meganyctiphanes norvegica is the main food item in the western Mediterranean Sea (Canese et al, 2006;Notarbartolo-di-Sciara et al, 2003;Orsi Relini and Giordano, 1992).…”
Section: Introductionmentioning
confidence: 98%